PENGARUH REKRUTMEN DAN PENEMPATAN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT.BANK RIAUKEPRI PEKANBARU - Muhammad Rafi; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Man power source is one of the important factors for companies that developed and developing human resources obtained through good recruitment and placement in the position/ right position in order to create maximum employee performance and able to support the achievement of corporate goals. PT.Bank Riaukepri Pekanbaru have noticed the recruitment, placement, and employee performance . But when PT.Bank Riaukepri pekanbaru recruitment company achievements decreased and increased when not doing recruitment and placement of employees there is a discrepancy. Of this phenomenon researchers interested to know the effect of recruitment and placement of employees on the performance of employees at PT Bank Riaukepri pekanbaruThe method used in this research is descriptive quantitative, data collection using the questionnaire, this study aims to determine the effect of recruitment and placement of employees on the performance of employees at PT Bank Riaukepri Pekanbaru, researchers using multiple linear regrensi analysis. X1 variable in this study is a Recruitment, X2 is the placement, and Y is Performance. the number of samples in this study were 48 people, the sampling technique is simple random sampling, sampling by means of the draw.The results showed the effect of variable recruitment and placement of employees on the performance of employees at PT Bank Riaukepri Pekanbaru, from analysis of multiple regrensi Y = 2284 + 0709 + 0258 X1 X2 + e. T test with t table at a significance level of 5 % ( 2 - tailed ) = 2.014, t = 4,821 X1, X2 = 2,416. Then there is positive and significant relationship between X1 to Y. And a positive and significant influence between X2 toward Y. Test f with f value count = 34 701 > f table = 3.204. Then simultaneously X1 and X2 influence on Y. And note X1 is a dominant factor of influence on Y. And the unknown value of r = 0.607 percent, so donations influence of X1 and X2 on Y by 60.7 %. And 39.3 % are influenced variables are not included in this equation.Keywords: Recruitment, Placement, and Performance.